GE_GERICHTE P/2282/2021 vom 29. Januar 2021 - GE Cour de justice (2021)
ORDONNANCE PÉNALE;OPPOSITION;DÉPART D'UN PAYS;DOMICILE À L'ÉTRANGER;FICTION DE LA NOTIFICATION;FEUILLE OFFICIELLE | CPP.356.al4; CPP.201; CPP.87.al4; CPP.88.al1; CPP.366; CPP.355.al2